Fusing Administrative Data to Combat the Opioid Crisis - Conway, Kevin P; Gourdet, Camille (International Journal of Population Data Science, 2018)
Opioid-related overdose deaths remain the leading cause of unintentional injury fatalities in the United States. State lawmakers have responded to this crisis by establishing a regulatory environment that extends various legal protections to persons who may help save the life of someone experiencing an opioid-related overdose. Most states now protect specific parties (e.g., doctors, pharmacists, first responders, laypersons) from civil or criminal liability who prescribe, dispense, possess or administer an opioid antagonist in accordance with the provisions of the state’s law. In addition to standing orders that facilitate access to opioid antagonists, many states offer legal protection to “Good Samaritans” seeking medical and emergency assistance for a person experiencing an overdose. Some states additionally mandate that addiction-treatment services be offered in conjunction with the dispensing of an opioid antagonist, whereas others designate revenue to purchase opiate antagonists or to fund treatment programs. Little is known about the potential impact of such regulatory actions on the opioid crisis. RTI’s Data Fusion Center seeks to meet this need by combining administrative data across sources and systems to inform research and policy. The current paper describes the Data Fusion Center and presents preliminary results from a study that predicts opioid-related overdose deaths based on the existence and strength of opioid-related state laws among 50 states from 2006 to 2016. Policy data were webscraped from state agencies, systematically coded, and associated with target outcomes sourced from CDC. Study findings may help inform lawmakers and stakeholders in prioritizing data-driven policy responses to the opioid crisis.